Comparative analysis of variation in African Bambara groundnut [Vigna subterranea (L) Verdc.] landraces assessed through seed traits - Uba, C.U.; Oselebe, H.O.; Tesfaye, A.A.; Agbo, C.U.; Abtew, W.G. (Elsevier, 2022)
Bambara groundnut [Vigna subterranea (L.) Verdc.] originated from the African continent and plays social-economic roles in regions where it is consumed. This study examined 297 landraces of African Bambara groundnut from four African regions (West, Central, East, and Southern) to estimate the extent of diversity in each population, identify useful seed traits for differentiation in the population and estimate association among seed quantitative traits using eight qualitative and seven quantitative seed traits. The result of seed qualitative traits showed considerable diversity in the African Bambara groundnut population with West African regions having the highest diversity (0.71) followed by Central Africa (0.64), East Africa (0.62), and Southern Africa (0.61). Heatmap analysis on the distribution of seed qualitative traits revealed that all the regions shared similarities in reference to the phenotypic classes of the traits with greater similarity found within the group. These groups were West and Central Africa as group A; while East and Southern Africa as group B. The descriptive statistics on seed quantitative traits revealed a wide range of variations within each population. Significant (p < 0.05) genetic variation was recorded among the landraces within each region for the most studied traits. Moderate heritability accompanied with high genetic advance was obtained on hundred seed weight in most of the studied regions. Factor analysis of mixed data (FAMD) in principal component analysis revealed that seed coat colour had strong discriminatory power in the crop characterization. FAMD in cluster analysis grouped the germplasm into three clusters with cluster II showing superiority for seed-related (seed length, seed width, and seed thickness) traits. The overall results confirmed that Bambara groundnut can be classified through seed morphology and considerable seed diversity depicted among the population that can be utilized in the future genetic improvement of Bambara groundnut.